The Molecular Pathology of Pre-Eclamptic Hypertension - Robin W. Carrell; Randy J. Read; Aiwu Zhou (Current Issues in Molecular Biology)
The central role of angiotensinogen in the control of blood pressure is revealed by a series of crystallographic structures, including complexes with renin. Specifically, the structures provide an understanding of the sequential molecular events that lead to the pre-eclamptic hypertensive crises of pregnancy. The release of the precursor vasopressor peptide from the amino-terminal tail of angiotensinogen appears to be modulated by a redox-sensitive disulphide bridge. Our findings indicate that the activation of the thiol-switch in the circulating maternal angiotensinogen occurs at the placental level in response to oxidative stress, exacerbated by placental insufficiency. We propose here that a contributory factor is the inherent redox stress accompanying the placental exchange of oxygenation between the haemoglobin of the mother (oxy-HbA) and the deoxygenated haemoglobin of the foetus (deoxy-HbF).